Al-Kairanawi’s methods of critique on bible: an analysis of ‘Izhar al-Haq’ - Wan Haslan Khairuddin; Indriaty Ismail; Jaffary Awang (Universiti Kebangsaan Malaysia, 2013)
Al-Quran is deemed to be the first text or charter which recognizes the existence of other religions in addition to asserting the truth of Islam and expose incoherent and the faults of otherwise. The facts set forth in the al-Quran, al-Kafirun 109: 1-6. Similarly, there are many verses in the Quran that deal with religions, whether samawi or wadha`i religions. In presenting religions, the Quran highlight various methods of criticism such [i] method of comparison such as comparing the truth and falsehood or comparing between monotheism and polytheism, [ii] presents the falsehood faith based on historical method, [iii] method of arguing by demanding supported evidence, creed or faith from its believer. The diversity critical method of al-Quran is a guide for scholars and Muslim intellectuals in dealing with propaganda of religions other than Islam through their works. The works Izhar al-Haq has written by Syeikh Rahmatullah al-Kairanawi (1818-1891) is subjected in this article. Discussion of this article focuses on al-Kairanawi's adaptation on the Quranic approach in criticizing the Bible; equation issues in Izhar al-Haq and the Quran; critical method by arguing and demanding textual evidences that are believed by the defendant. The methodology adopted in this study is content analysis and comparison between the approaches of the Izhar al-Haq and the Quran. Finally, the article concludes that al-Kairanawi approach in his Izhar al-Haq is accordance with the approach of the Quran in criticizing the Bible.